Sensus Amoris: the Sense of Love in Two Texts of William of Saint Thierry - Ryan, Patrick (Cistercian studies quarterly, 2005)
This article examine how one twelfth-century Cistercian author, describes the human person's experience of God, especially by considering how he uses the term sensus amoris in two passages of his works, one of which occurs in his "Meditation Three" and the other in "The Mirror of Faith." In Meditation Three and Speculum Fidei, the author has shown how the search for God can lead one from the external senses to the sensus amoris, the sense of love of the soul, and in this way to union with God in love. If, in the Cistercian tradition, one is trying to move toward this union with God in love, will he not also have to ponder God ever more profoundly.